Pengaruh Kualitas Produk dan Kepuasan Pelanggan terhadap Daya Saing KFC dan Sabana pada ISO-9000 - Nashwa Mutiara Putri; Devia Wulandari; Adeta Suci Anggraini; Nurul Hikmah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the impact of product quality and customer satisfaction on the competitiveness of KFC and Sabana, considering the implementation of ISO 9000 standards. Using a survey method, data were collected from 30 respondents who are customers of both brands. The analysis results indicate that product quality has a significant effect on customer satisfaction, which in turn contributes to enhancing the competitiveness of both companies. KFC, known for its consistency and product innovation, demonstrates higher competitiveness compared to Sabana. However, Sabana also shows commendable efforts in improving quality and customer satisfaction. These findings emphasize the importance of implementing ISO 9000 quality management standards in enhancing product quality and customer satisfaction as key factors in maintaining competitiveness in the fast-food industry. This research provides insights for companies to focus more on quality improvement and service for long-term success.